2021
DOI: 10.1002/agj2.20527
|View full text |Cite
|
Sign up to set email alerts
|

Ridge‐furrow rainfall harvesting planting and its effect on soil erosion and soil quality in sloping farmland

Abstract: Ridge-furrow rainfall harvesting (RFRH) planting can improve crop productivity through enhancing water use efficiency. However, effects of long-term use of RFRH on soil erosion and soil quality in sloping farmland are not well understood. This experiment was conducted with a two-factor split plot design, with the main plot having a slope of 5˚and 10˚. The sub-plots followed three planting patterns: contour ridge-furrow planting without mulching (CK), contour ridge film mulching and furrow straw mulching (T1), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Xin et al. (2020) studied the effect of ridge‐furrow rainfall harvesting planting on soil erosion and soil health. They concluded that ridge film mulching and furrow straw mulching are effective methods to alleviate drought, water shortage, and soil erosion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Xin et al. (2020) studied the effect of ridge‐furrow rainfall harvesting planting on soil erosion and soil health. They concluded that ridge film mulching and furrow straw mulching are effective methods to alleviate drought, water shortage, and soil erosion.…”
Section: Resultsmentioning
confidence: 99%
“…Results showed that Liuyang had high resistance to Imidacloprid (C 9 H 10 ClN 5 O 2 ), and moderate resistance to Acetamiprid (C 10 H 11 ClN 4 ) and Cyhalothrin (C 23 H 19 CIF 3 NO 3 ). Longshan, Liyang, and Guiyang had low to moderate resistance to Phoxim (C 12 H 15 N 2 O 3 PS) Xin et al (2020). studied the effect of ridge-furrow rainfall harvesting planting on soil erosion and soil health.…”
mentioning
confidence: 99%
“…The experiment was conducted in the Fuxin Scientific Observation Station of Agricultural Environment and Cultivated Land Conservation, Ministry of Agriculture, in the Northwest Liaoning Province (42 • 06 N, 121 • 75 E, Shazalan Village, Fuxin Town, Fuxin Mongolian Autonomous County, Fuxin City, Liaoning Province), which was affiliated to the Institute of Crop Cultivation and Farming System, Liaoning Academy of Agricultural Sciences. The soil type in Fuxin City is mainly cinnamon soil, belonging to the transitional soil from the brown forest soil to the chestnut soil, which is neutral (surface layer) to slightly alkaline (bottom layer), low in soil porosity and soil infiltration, poor in soil water retention ability, low in organic matter content, and poor in vegetation coverage in whole areas [12]. The sloping farmlands in this area account for 41.69% of the total cultivated land area, most of which are gentle sloping farmlands with a slope between 5 • and 15 • , accounting for 78.26% of the total sloping farmlands area.…”
Section: Experiments Fieldmentioning
confidence: 99%
“…Among these measures, the ridge film and furrow seeding have been identified as particularly effective, especially in arid areas with low rainfall. This technique involves creating ridges and furrows in the land and planting crops in the furrows [12][13][14][15]. The ridge film and furrow seeding could quickly form a confluence, making the water stored in the root zone of the crops significantly improve the use efficiency of water and nutrients and further increasing the crops yield [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…On the Loess Plateau in China, sloping land is the main type of cultivation land due to its topography. Owing to the influence of anthropogenic farming, the bare ground area is large, and under the impact of raindrops during the rainy season, the soil structure is more easily destroyed than that of other site types, resulting in a reduced soil infiltration capacity, increased runoff and enhanced soil erosion (Li et al, 2020; Wang, Ma, & Wu, 2017; Xin et al, 2020). Studies have indicated that approximately 60% of watershed runoff and sediment originates from sloping land due to natural and human factors, which seriously threatens the ecological environment and sustainable development of agriculture in the region (Keesstra et al, 2016; Wang, Dalabay, et al, 2017).…”
Section: Introductionmentioning
confidence: 99%